2004
DOI: 10.1590/s1516-35982004000400017
|View full text |Cite
|
Sign up to set email alerts
|

Características da carcaça de novilhos 5/8 Nelore-3/8 Charolês abatidos em diferentes estádios de desenvolvimento

Abstract: RESUMO -Foram avaliadas as características quantitativas das carcaças de novilhos 5/8 Nelore-3/8 Charolês terminados em confinamento até estes atingirem o peso médio de abate (P) de 425, 467 e 510 kg. Os novilhos apresentaram ao início do confinamento idade média de 660 dias, peso de 361 kg e estado corporal de 2,9 pontos. A dieta oferecida, com relação volumoso:concentrado de 60:40 na base matéria seca (MS), continha 10,25% de proteína bruta e 72,18% de nutrientes digestíveis totais. O volumoso foi silagem de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 7 publications
3
16
2
14
Order By: Relevance
“…In general, carcasses with better fat cover degree present lower loss during cooling, resulting in negative correlation between the two variables, according to the results published by Restle et al (1997) and Arboitte et al (2004b) and the present study, presenting significant correlation (r= -0.45). According to Restle et al (1997), the variation in shrinkage loss is also associated with the oscillations that occur in the cold chamber (temperature, wind speed, number of carcasses).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…In general, carcasses with better fat cover degree present lower loss during cooling, resulting in negative correlation between the two variables, according to the results published by Restle et al (1997) and Arboitte et al (2004b) and the present study, presenting significant correlation (r= -0.45). According to Restle et al (1997), the variation in shrinkage loss is also associated with the oscillations that occur in the cold chamber (temperature, wind speed, number of carcasses).…”
Section: Resultssupporting
confidence: 82%
“…Feed conversion (FC) worsened as the slaughter weight increased, corroborating the literature (Costa et al, 2002a;Arboitte et al, 2004a;Cruz et al, 2004a). Costa et al (2002a) reported that with increase in animal weight feed efficiency is lowered, and this is due to the differences in the composition of weight gain.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations